Einkorn Wheat Malting Quality - Lenka Sachambula; Ivo Hartman; Vratislav Psota (Kvasný průmysl, 2015)
Standard malting technology was adapted for malting of einkorn wheat. The aim was to find the optimal variant of malting while maintaining traits decisive for high quality of malt made from einkorn wheat. Basic characters of wheat grain were assessed and the sample was malted. Three different malting times (120, 144, and 168 hours) and three degrees of steeping (43, 45, and 47%) were applied. Besides basic traits decisive for einkorn wheat malt quality, a number of special parameters were also studied. Wheat samples were evaluated with the method used for the evaluation of malting barley. In some quality parameters, einkorn wheat achieved comparable results as malting barley.